Treatment with Continuous Subcutaneous Insulin Infusion in Adolescence – Mother´s views - Lima, Lígia (2023)
Background: type 1 Diabetes Mellitus is a chronic disease that affects mostly children and young people. In its treatment, insulin therapy is essential. Insulin can be administered by Multiple Daily Injections (MDI) or by continuous subcutaneous insulin infusion (CSII) system. The latter has advantages, but the adaptation process is demanding. Objective: to identify mother’s views regarding the PSCI system in the treatment of DM1 of adolescents. Methodology: qualitative descriptive and exploratory study. Data collection was performed by semi-structured interview with 10 mothers of adolescents with DM1 who underwent treatment for DM1 with CSII.  Its analysis was performed by Bardin's content analysis method. Results: from the analysis of the interviews, four categories emerged: The transition to CSII, Adolescent and family well-being, Adolescent autonomy and Limitations of the device and respective subcategories that expose the perception of mothers of adolescents with DM1 about treatment with CSII. Conclusion: treatment with CSII provides a better quality of life for adolescents and their families and favors the autonomy of adolescents. The adaptation process poses challenges and the support of health professionals is essential. Some limitations were identified in the device that hopefully will be overcome by the current technological innovations.